Discrimination against migrants in Austria: An experimental study - Doris Weichselbaumer (Johannes Kepler University of Linz, Department of Economics, 2015)
In this paper, I experimentally examine the employment opportunities of Austrians with and without migration background. Applications of candidates with a Serbian, Turkish, Chinese, Nigerian and no migration background are sent in response to job openings. Previous experiments have indicated ethnicity via the name of an applicant, however employers may not always correctly perceive this signal. Since photographs are a requirement for applications in the German speaking context, this study uses a novel approach to signal ethnic background and employs carefully matched photos as distinct visual cues. While results document employment discrimination for all groups with migration background, it is most pronounced for applicants with an African, i.e. Nigerian, background. To explain why and when discrimination occurs, a battery of firm and job specific characteristics are examined (e.g. whether team or customer contact is part of the job description). However, these help little to explain the actual level of discrimination. Discrimination in Austria therefore seems to be a general phenomenon driven by employers' preferences that is barely affected by situational variables.
Keywords: C93; J15; J71; 330; migration; discrimination; hiring; correspondence testing